2001
DOI: 10.1128/jb.183.4.1184-1194.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Silent gal Genes in the lac-gal Regulon of Streptococcus thermophilus

Abstract: Streptococcus thermophilus strain CNRZ 302 is unable to ferment galactose, neither that generated intracellularly by lactose hydrolysis nor the free sugar. Nevertheless, sequence analysis and complementation studies with Escherichia coli demonstrated that strain CNRZ 302 contained structurally intact genes for the Leloir pathway enzymes. These were organized into an operon in the order galKTE, which was preceded by a divergently transcribed regulator gene, galR, and followed by a galM gene and the lactose oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
110
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 60 publications
(49 reference statements)
8
110
3
Order By: Relevance
“…Mutations to a galactose-positive phenotype do not result in constitutive expression of the gal genes, which strongly suggests that S. thermophilus was Gal positive and became Gal negative in the recent past (30). Currently, the Gal-negative phenotype has been ascribed to a defect in the induction mechanism of GalK, which seems to be the rate-limiting enzyme of the Leloir pathway (2).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Mutations to a galactose-positive phenotype do not result in constitutive expression of the gal genes, which strongly suggests that S. thermophilus was Gal positive and became Gal negative in the recent past (30). Currently, the Gal-negative phenotype has been ascribed to a defect in the induction mechanism of GalK, which seems to be the rate-limiting enzyme of the Leloir pathway (2).…”
mentioning
confidence: 98%
“…However, under appropriate selective conditions, such as limited lactose and excess galactose concentrations, Gal-positive derivatives of S. thermophilus can be obtained which ferment galactose and possess Leloir enzyme activities (11,14,22). It has been shown that the Gal-negative S. thermophilus strain CNRZ 302 contains structurally intact genes for the Leloir pathway enzymes, but that they are weakly transcribed, while independently isolated Gal-positive mutants contain up mutations in the gal promoter (30). The function of GalR has been determined as a transcriptional activator of both the gal and lac operons, which negatively regulates its own expression (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a moderate thermophile, it is phylogenetically related to the more mesophilic lactococci and has a comparable low G+C ratio (40%). Genes coding for metabolic pathways involved in sugar catabolism (Poolman et al 1989;Vaughan et al 2001), protein and peptide utilization (Fernandez-Espla et al 2000;Garault et al 2002), polysaccharide production (Almirón-Roig et al 2000), the stress response system (Perrin et al 1999), and phage resistance mechanisms (Solow & Somkuti 2000;Burrus 2001) have been sequenced and characterized. Although most strains do not harbor plasmids, other mobile elements have been reported (Guedon et.…”
Section: Streptococcus Thermophilus Lmd-9 (Contributed By Robert Hutkmentioning
confidence: 99%
“…The glucose moiety is further metabolized via glycolysis, whereas the galactose moiety follows different pathways depending on the particular LAB. While some thermophilic strains of LAB (e.g., Lactobacillus bulgaricus and Streptococcus thermophilus) are known to release the galactose moiety of lactose into the medium, other LAB (e.g., Lactobacillus helveticus, Leuconostoc lactis and Streptococcus salivarius) metabolize this saccharide via the Leloir pathway (de Vos, 1996;Poolman, 1993;Vaughan et al, 2001). This pathway was one of the first central metabolic pathways to be discovered, by L. F. Leloir and coworkers in the early 1950s.…”
Section: Lactose Permease-β-galactosidase Systemsmentioning
confidence: 99%